2022
DOI: 10.3389/fpls.2022.1030584
|View full text |Cite
|
Sign up to set email alerts
|

PacBio full-length sequencing integrated with RNA-seq reveals the molecular mechanism of waterlogging and its recovery in Paeonia ostii

Abstract: Paeonia ostii, a widely cultivated tree peony species in China, is a resourceful plant with medicinal, ornamental and oil value. However, fleshy roots lead to a low tolerance to waterlogging in P. ostii. In this study, P. ostii roots were sequenced using a hybrid approach combining single-molecule real-time and next-generation sequencing platforms to understand the molecular mechanism underlying the response to this sequentially waterlogging stress, the normal growth, waterlogging treatment (WT), and waterlogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…AtMYB44 in Arabidopsis activates the scavenging system and inhibits ROS production ( Gu et al., 2019 ). MYB TFs are considered to be the second largest TF family responding to flooding stress, and it has been reported that MYB TFs play a key regulatory role in flooding stress in many plants, and genes for WRKY and MYB are induced to be expressed under flooding conditions and are highly responsive ( Zhang et al., 2022 ). Among the Arabidopsis bZIP gene family, AtbZIP2 can respond to a variety of stresses such as drought, heat, low temperature, and high salt ( Weltmeier et al., 2009 ), which led to the hypothesis that the bZIP gene family may be a key transcription factor for the stress tolerance of H. compressa.…”
Section: Discussionmentioning
confidence: 99%
“…AtMYB44 in Arabidopsis activates the scavenging system and inhibits ROS production ( Gu et al., 2019 ). MYB TFs are considered to be the second largest TF family responding to flooding stress, and it has been reported that MYB TFs play a key regulatory role in flooding stress in many plants, and genes for WRKY and MYB are induced to be expressed under flooding conditions and are highly responsive ( Zhang et al., 2022 ). Among the Arabidopsis bZIP gene family, AtbZIP2 can respond to a variety of stresses such as drought, heat, low temperature, and high salt ( Weltmeier et al., 2009 ), which led to the hypothesis that the bZIP gene family may be a key transcription factor for the stress tolerance of H. compressa.…”
Section: Discussionmentioning
confidence: 99%
“…TFs hold significant importance in the responses of plants to abiotic stressors [ 49 , 50 , 51 , 52 ]. Previous studies have established that members of the C2H2, AP2/ERF-ERF, bHLH, and NAC TF families play crucial roles in the abiotic stress responses of plants and their ability to tolerate waterlogging stress [ 53 , 54 , 55 , 56 , 57 , 58 ]. For instance, C2H2 and NAC TFs contribute to maintaining iron homeostasis in waterlogged rice, a region known for Fe 2+ toxicity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%